Study of Gas Resources Utilization of Tangguh, Masela, and Kasuri Blocks for East Indonesia Regional Development - Tutuka Ariadji; Luky Yusgiantoro; D Susanto; D Sunarjanto; D Sismartono; W A Akbar; Wisnu P Taher; A Arsegianto (Indonesian Journal of Energy, 2018)
This study is intended to evaluate, analyze and give recommendations for prudently utilizing gas production to maximize regional economic developments. A method to relate sectors and inter-regions, i.e., Inter-regional Input-Output (IRIO) Model, is employed to predict the impact of the upstream potential on the down stream. This techno-economic study examines the allocated gas from three gas field blocks altogether at Maluku and West Papua Provinces, i.e., Tangguh, Masela, and Kasuri, to supply the demands of (1) power plants; (2) fertilizer industries, and (3) petrochemicals industries. This study identifies development processes, investment parameters from pre-construction to operation, implementation parameters, and output parameters, both for the upstream and downstream sectors during 2016-2035. The IRIO model uses the 2010 IRIO Table published by BAPPENAS which consists of 35 sectors and 35 provinces. The shock data used to estimate the economic impacts include those data on infrastructure (CAPEX, OPEX, and supporting facilities), energy consumption (per kWh, per ton fertilizer, and per petrochemical product), workforce, and investments at a particular time. Six simulation modeling scenarios were developed to forecast the future performance of Gross Domestic Product (GDP)/Regional Gross Domestic Products (GRDP), Community Income, and Employment of 4 provinces in Eastern Indonesia. The results indicate that the regional economy could grow significantly by providing electricity first. Hence, the Petrochemical Industry gives more contribution than the Fertilizer Industry. The contribution (compared to BAU condition) increases sharply before taking a peak period and then declines in the year 2025. The best scenario results in a rise of the regional GDP at about 19 percent, wages at about 20 percent, and employment at about 55 percent. Maluku Province deserves the most economic improvement followed by West Papua Province. North Maluku and Papua provinces are not as well-off as those two provinces although there has been an indication of some employment in North Maluku Province. JEL Classification: E23